Small iminium ions block gramicidin channels in lipid bilayers. - Hemsley, G (1991)
Guanidinium and acetamidinium, when added to the bathing solution in concentrations of approximately 0.1M, cause brief blocks in the single channel potassium currents from channels formed in planar lipid bilayers by gramicidin A. Single channel lifetimes are not affected indicating that the channel structure is not modified by the blockers. Guanidinium block durations and interblock times are approximately exponential in distribution. Block frequencies increase with guanidinium concentration whereas block durations are unaffected. Increases in membrane potential cause an increase in block frequency as expected for a positively charged blocker but a decrease in block duration suggesting that the block is relieved when the blocker passes through the channel. At low pH, urea, formamide, and acetamide cause similar blocks suggesting that the protonated species of these molecules also block. Arginine and several amines do not block. This indicates that only iminium ions which are small enough to enter the channel can cause blocks in gramicidin channels.